High sensitivity differential scannning calorimeter (HSDSC) technique for assaying ginger oleoresin - Morad, Norazian; Abd. Aziz, Mustafa Kamal (Centre of Lipids Engineering And Applied Research (CLEAR), Universiti Teknologi Malaysia, 2006)
Thermal analysis that is DSC ‘heat-flux’ type was studied as additional or supportive technique to the analytical technique commonly used such as chromatographic, spectroscopic and combination of chromatographic-spectroscopic. Two medicinal plants of Zingiberaceae, that is Zingiber officinale Roscoe (ginger) and Zingiber zerumbet Smith (wild ginger) were investigated. The dried rhizomes of ginger were extracted using solvent extraction techniques to produce crude product (oleoresin) while the fresh rhizomes of wild ginger were extracted using hydrodistillation to produce the essential oil. The major compounds were separated and purified by means of several chromatographic techniques including vacuum column chromatography, gravity column chromatography and preparative thin layer chromatography. The structures were elucidated using spectroscopic methods including 1 H NMR, 13C NMR, IR, GC and GC-MS. Two pure compounds were isolated from Z. officinale oleoresin and identified as 6-gingerol (brownish viscous liquid) and 6-shogaol (yellowish viscous liquid), while zerumbone (white crystals) was isolated from Z. zerumbet essential oil. The crude product as well as the pure compounds were analysed by using DSC technique. This method can be used to identify the major compound in crude product based on qualitative investigation of thermal behaviour (melting point, Tm and heat of fusion, ?Hf ). DSC can also estimate the purity of a substance based on the shape and temperature of the DSC melting endotherm. Sharp peak indicated pure compound while broad peak showed a mixture of various compounds.